Most asked questions about geosynthetic canal linings: do they work? and how much do they cost? - Haynes, Jack, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
The Bureau of Reclamation (Reclamation) is collaborating with several irrigation districts in central Oregon to demonstrate and evaluate various canal linings under actual field conditions. This paper shows the results of more than 7 years of field testing and includes a series of photographs showing the subgrades, construction, and required maintenance. This paper also examines the effectiveness of the various geosynthetics and other materials to control seepage and compares construction costs. Uncontrolled field testing of 29 types of geosynthetic canal liners exposed the various materials to very harsh conditions including freeze/thaw, wet/dry, direct and indirect sunlight, extreme rocky subgrades, wildlife (elk, deer, rodents, cattle, etc.) and man. Canals in this study had fractured basalt bottoms and typically lost 35 to 50 percent of the flow to seepage. Preconstruction seepage rates as determined by full-scale ponding tests ranged from 0.6 to 4.2 ft3/ft2-day. Following the installation of the linings, average seepage rates were reduced to less than 0.1 ft3/ft2-day.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.